Indigenous Women and the United Nations System - United Nations Department of Economic; Social Affairs (United Nations, 2007)
Despite their enormous assets and contribution to society, indigenous women still suffer from multiple discrimination, both as women and as indigenous individuals. They are subjected to extreme poverty, trafficking, illiteracy, lack of access to ancestral lands, non-existent or poor health care and to violence in the private and the public sphere. The present publication contains cases submitted by the different UN agencies about their work with indigenous women in Africa, Asia and Latin America.